The self-association of High Mobility Group Box 1 (HMGB1): Implications for interaction with Receptor for Advanced Glycation End-products (RAGE) and DNA - Anggayasti, Wresti Listu (Curtin University, 2015)
High Mobility Group Box 1 (HMGB1) plays key roles in inflammatory diseases including cancer and diabetes. Intracellularly, HMGB1 binds DNA and assists transcription. Extracellularly, HMGB1 promotes inflammatory responses by binding to receptors such as the Receptor of Advanced Glycation End-products (RAGE). HMGB1 specifically self-associates in Surface Plasmon Resonance (SPR). The self-association is markedly influenced by ionic strength, redox, zinc ions, and pH. The role of HMGB1 self-association in binding DNA or RAGE is discussed.